2017
DOI: 10.1111/epi.13809
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic protection against acute flurothyl‐induced seizures by adjuvant treatment of the ketogenic diet with the type 2 diabetes drug pioglitazone

Abstract: Objective We have previously found that the transcription factor PPARγ contributes to the mechanism of action of the ketogenic diet (KD), an established treatment for pediatric refractory epilepsy. We have found that the KD increases brain PPARγ and that inhibition or genetic loss of PPARγ prevents the antiseizure effects of the KD on (1) acutely induced seizures in non-epileptic mice and (2) spontaneous recurrent seizures in epileptic mice. Here, we tested the hypothesis that adjuvant treatment of KD-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…We previously found that the KD increased brain nuclear PPARγ2 and that pharmacological or genetic loss prevented KD antiseizure efficacy against chemically induced acute seizures in non-epileptic mice and spontaneous recurrent seizures in epileptic Kcna1 −/− mice (Simeone et al, 2017c). Further supporting an interaction between the KD and PPARγ, co-administration of an ineffective low ratio KD and low dose of a PPARγ agonist provided significant seizure protection (Simeone et al, 2017b). Here, we have begun to explore potential downstream effectors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously found that the KD increased brain nuclear PPARγ2 and that pharmacological or genetic loss prevented KD antiseizure efficacy against chemically induced acute seizures in non-epileptic mice and spontaneous recurrent seizures in epileptic Kcna1 −/− mice (Simeone et al, 2017c). Further supporting an interaction between the KD and PPARγ, co-administration of an ineffective low ratio KD and low dose of a PPARγ agonist provided significant seizure protection (Simeone et al, 2017b). Here, we have begun to explore potential downstream effectors.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, we demonstrated that the KD reduces seizures by 75% and increases lifespan of Kcna1 -null ( Kcna1 −/− ) mice, a model of severe, chronic, temporal lobe epilepsy and sudden unexpected death in epilepsy (Kim et al, 2015; Simeone et al, 2016; Simeone et al, 2017c). Further studies indicated that a splice variant of the nutritionally-regulated transcription factor peroxisome proliferator activated receptor gamma2 (PPARγ2) is involved in the anti-seizure mechanism of the KD (Simeone et al, 2017b,c). Among the wide-array of genes regulated by PPARγ, antioxidants such as catalase may have prominent roles in KD neuroprotective and antiseizure effects.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is rife with examples of indirect ferroptotic signs including iron accumulation in various animal models of epilepsy. Biochemical evidence also supports the occurrence of ferroptosis in the etiology of epilepsy as lipid degradation products such as 4-HNE and MDA are found to be enormously augmented (Willmore et al, 1978a,b; Manev et al, 1998; Abdallah, 2010; Mao et al, 2014; Pecorelli et al, 2015; Zhu et al, 2016; Simeone et al, 2017; Zou et al, 2017). And reduction of iron content by iron chelation agent (e.g., deferoxamine) suppresses epileptic seizures (Zou et al, 2017).…”
Section: Is Redox-associated Ferroptosis Important In Epilepsy?mentioning
confidence: 87%
“…Lipid peroxidation affects membrane fluidity and permeability, producing many cytotoxic and reactive by-products. Lipid by-products have been found to increase in experimental models of epilepsy, further propagating oxidative damage [ 13 , 35 , 36 , 37 , 38 ]. In particular, lipid peroxides increased in the hippocampus of rat models during the acute phase of status epilepticus and persisted for several hours after spontaneous recovery, suggesting a wide therapeutic window for the use of antioxidants in the treatment of epilepsy [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%